Huge lipoblastoma engulfing Hunter's canal in a 3-year-old male child - Vinit Kumar Thakur; Ritesh Runu; Saurav Srivastava (Wolters Kluwer -Medknow Publications, 2024)
Lipoblastoma in children is not an unheard entity. It is normally a benign mass seen in extremities and rarely involves deeper structures. Its complete excision is warranted to alleviate the symptoms and avoid future recurrence. We report an unusual case of huge lipoblastoma engulfing Hunter's canal in a 3 years' male child.